Implementation of Macro Ergonomic Participatory In Physical Work Environment: A Literature Review - Candra, Muhammad; Ginting, Rosnani; Nurul Huda, Listiani (Jurnal Sistem Teknik Industri, 2023)
All types of work must have potential hazards in the work, namely work-related illnesses or work accidents. The level of potential occupational hazard is influenced by the type of production activity, the technology used, the materials used, the design and construction environment, and the quality of management and workers. Musculoskeletal disorders, caused not only by aging but also by unergonomic settings of the equipment used, are one of the frequent occupational diseases caused by worker-job mismatch. This study aims to review the participatory macroergonomics literature based on the collected references on the development and application of creating ergonomic physical work environments. Participatory methods are methods that aim to find solutions agreed upon by managers, workers and ergonomics experts, and the result of this research is the ergonomic design of work environments.